Treatment default among pulmonary tuberculosis patients at an urban slum in South-Eastern Nigeria - Nwachukwu, Ndubuisi O.; Onyeagba, Azu R.; Onwuchekwa, Elendu C.; Uche, Okoronkwo C.; Esther, Ulasi A. (International Journal of Research in Medical Sciences, 2017)
Background: Anambra State is one of the States in Nigeria with a high rate of treatment default. The objectives were to examine default from treatment among newly diagnosed pulmonary tuberculosis patients and identify reasons for default. Methods: This prospective observational study was conducted at Okpoko in Ogbaru local government area of Anambra state. A total of 166 patients participated. Diagnosis of pulmonary tuberculosis was based on microscopy. Patients were treated using the standard 6-month regimen recommended by WHO. Results: A treatment default rate of 13.3% was observed. Default was higher in males (15.7%) and in patients aged < 35 years old (P<0.05). Exactly 9 (13.8%) defaulters lived >5km radius from treatment centers versus 3 (12.9%) who lived <5km radius from treatment centers (P<0.05). Majority of patients 17 (77.3%) defaulted during the continuation phase of treatment. The main reasons for default were attributed to harsh attitude of care providers (59.1%), resolution of symptoms (54.5%) migration (36.4%) and poverty (36.4%). Conclusions: Treatment default was high (13.3%) and majority of patients defaulted during the continuation phases. Periodic supervision of community care providers and enhanced counselling of young patients will reduce patient default from treatment.